A new framework for the analysis of inequality - Flavio Cunha; James Joseph Heckman (Institute for the Study of Labor (IZA), 2007)
This paper presents a new framework for analyzing inequality that moves beyond the anonymity postulate. We estimate the determinants of sectoral choice and the joint distributions of outcomes across sectors. We determine which components of realized earnings variability are due to uncertainty and which components are due to components of human diversity that are forecastable by agents. Using our tools, we can determine how policies shift persons across sectors and outcome distributions across sectors
urn:nbn:de:101:1-20080425303
Keywords: 330; Einkommensverteilung; Soziale Mobilität; Disparitätsmaß; Politischer Wandel; Sozialer Wandel; Messung; Theorie; USA